Understanding Family Communication and Peer Group in Decision of Wearing Hijab - Nindha Rahmayantie, Erieke; Budi Lestari, SU, Dr. Dra. Sri (Interaksi Online, 2016)
Hijab has become trend and lifestyle for the muslim women. Started many young people who uses hijab with some consideration is to run religious orders, become more syar’i or just following the trend. In this case, youth’s decision making to wear hijab assumed that inspired by peer group and family. This descriptive qualitative research aims to describe that family and peer group has contribution in youth’s decision making to wear hijab. Subject of this research is moslem’s teenager, age 18 – 22 years, wear hijab within the past year (since 2015), better use hijab syar’i or modern. Approach in phenomenology, this research is based on paradigm constructivism. This research use Ethic Dialogic Theory who focus on I – Thou relationship that provide opportunities for each individual to express their opinions, and Symbolic Interactionism Theory which refers to a verbal and non verbal symbol that family or peer group used to contribute youth’s decision making of wear hijab. The results showed that in fact the family and peer groups contribute to the decision making process of wearing hijab. individuals have the opportunity to express and decide their own choices. Family and peer group plays a role in providing advice and consideration in decision making process of wearing hijab. Type of family, parenting style that applied by parents and family culture influence on decision making process. In family, informant are closer to the mother figure that is considered provide more advice. Close family communication relationship contributes that familiarity can bring an openness to tell each other that eventually will be material of the decision. While in communication with peer group, verbal and nonverbal comments are given by peers to contribute in decision making of wearing hijab. In a group of peers which the members are improve themselves and bound in friendship commitment further contribute in decision of wearing hijab. Friendship functions play a role in youth’s decision making process that is togetherness, simulation, physical support, the support of ego, social comparison and intimacy or attention. All the informant relationship with peer group has become the stage of friendship. Inspiration figure was also instrumental in giving confidence in wearing hijab. in addition to family members and peers, public figure also inspired many informant of wearing hijab.